COMBINING OF HERRINGBONE TECHNIQUE WITH THINK PAIR SHARE (TPS) STRATEGY IN READING COMPREHENSION - Uhdatul Islamiyah; Mustain Mustain (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2022)
This research investigated combining of Herringbone technique with Think Pair Share (TPS) strategy in reading comprehension. The design of this research was quasi-experimental with non-equivalent groups pretest-posttest. Two groups were used in the study; the experimental and control groups were given different treatments. The researcher taught the experimental group using the Herringbone technique with the TPS strategy, while the researcher taught the control group using the conventional method. The population of this study was the seventh grade of Junior High School in Bangkalan. The data were obtained by administering the reading test to two intact groups. The research was started by giving pre-tests, treatments, and post-tests to experimental and control groups. The data of the test were analyzed by using the analysis of covariance (ANCOVA). Results indicated that combining of herringbone technique with the TPS strategy was effective than the conventional technique. However, when examined in terms of post-test, both showed a statistically significant difference in reading comprehension. Based on the findings of this research, combining herringbone with think pair share appeared to be a plausible alternative for teaching English reading comprehension to the seventh-year students of Junior High School in Bangkalan.